Experience with left ventricular assist device usage in the treatment of end-stage heart failure - B.M. Todurov; G.I. Kovtun; I.M. Kuzmich; M.V. Goncharenko; A.M. Druzhyna; A.O. Shpachuk; O.M. Postupalsky; S.O. Sheludko; S.M. Sudakevych; O.V. Stanyshevskyi; A.Yu. Melnyk (Кардіохірургія та інтервенційна кардіологія)
Heart failure potentially developing in most of heart diseases is a progressive process associated with high morbidity and mortality. Almost 3/4 of patients die within five years after first hospitalization because of heart failure. The main treatment for patients with terminal heart failure is heart transplantation. Left ventricular assist device is a main alternative to heart transplantation. We present case of long-term mechanical support applied in patients with heart failure class IV NYHA, refractory to medical therapy. Long-term implantation of mechanical heart support system may serve as an effective bridge to heart transplantation in patients with advanced congestive heart failure.